2014
DOI: 10.1136/bmjopen-2013-004391
|View full text |Cite
|
Sign up to set email alerts
|

UK doctors’ views on the implementation of the European Working Time Directive as applied to medical practice: a quantitative analysis

Abstract: ObjectivesTo report on doctors’ views, from all specialty backgrounds, about the European Working Time Directive (EWTD) and its impact on the National Health Service (NHS), senior doctors and junior doctors.DesignAll medical school graduates from 1999 to 2000 were surveyed by post and email in 2012.SettingThe UK.MethodsAmong other questions, in a multipurpose survey on medical careers and career intentions, doctors were asked to respond to three statements about the EWTD on a five-point scale (from strongly ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Accordingly, for our next scheduled surveys, which were of the qualifiers of 1999 and 2000, undertaken in 2012, we added a specific section on views about the EWTD, inviting all doctors to reply to it. We report on this in the accompanying paper 25. In summary, in that paper we show that the implementation of the EWTD is not widely endorsed.…”
Section: Discussionmentioning
confidence: 85%
“…Accordingly, for our next scheduled surveys, which were of the qualifiers of 1999 and 2000, undertaken in 2012, we added a specific section on views about the EWTD, inviting all doctors to reply to it. We report on this in the accompanying paper 25. In summary, in that paper we show that the implementation of the EWTD is not widely endorsed.…”
Section: Discussionmentioning
confidence: 85%
“…More negative views were reported by doctors in surgical specialities. 33 How doctors in Norway perceive the relationship between the quality of postgraduate training for junior doctors and the actual work-week is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings on the implementation of the Directive accord with our previous study which found strong disagreement that the Directive had benefited senior doctors or the NHS. 10 Other studies and reviews have also reported reduced opportunities for training. 6 , 7 , 11 One study found that junior doctors do not want to work longer hours and do not believe that the Directive has had an adverse effect on their training.…”
Section: Discussionmentioning
confidence: 99%
“…In two previous studies, in 2012, of doctors who had experience of working before and after the implementation of the Directive, we found that doctors were critical of the Directive. 10 , 11 Only one-third of doctors agreed that the Directive had benefited junior doctors (31%). Much smaller percentages agreed that the Directive had benefited senior doctors (12%) or the NHS as a whole (9%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation